2015
DOI: 10.1111/andr.12067
|View full text |Cite
|
Sign up to set email alerts
|

Age and markers of Leydig cell function, but not of Sertoli cell function predict the success of sperm retrieval in adolescents and adults with Klinefelter's syndrome

Abstract: SUMMARYMicrosurgical testicular sperm extraction (mTESE), combined with intracytoplasmic sperm injection (ICSI) represents a chance for azoospermic men with Klinefelter 0 s syndrome (KS) to father children. The objective of this study was to identify predictive factors for the success of mTESE from adolescents and adults with KS. The clinical data of 50 late pubertal adolescents (13-19 years) and 85 adult patients (20-61 years) with non-mosaic KS, who underwent mTESE, were analysed with respect to factors, pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
96
3
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(114 citation statements)
references
References 41 publications
6
96
3
9
Order By: Relevance
“…(ii) The experience of the surgeon and the biologist is important for the success of TESE. Micro-TESE performed by trained surgeons results on average in higher sperm retrieval rate than open biopsy; and (iii) The age range giving rise to higher chances of sperm retrieval is 15-30 years (Plotton et al, 2015;Rohayem et al, 2015). Conversely, some important issues remain to be investigated properly:…”
Section: Fertilitymentioning
confidence: 99%
See 1 more Smart Citation
“…(ii) The experience of the surgeon and the biologist is important for the success of TESE. Micro-TESE performed by trained surgeons results on average in higher sperm retrieval rate than open biopsy; and (iii) The age range giving rise to higher chances of sperm retrieval is 15-30 years (Plotton et al, 2015;Rohayem et al, 2015). Conversely, some important issues remain to be investigated properly:…”
Section: Fertilitymentioning
confidence: 99%
“…3 Identification of predictive markers of successful TESE would be helpful and should be developed. Sabine Kliesch emphasized that such multicenter trials would require standardization of the techniques used in the participating centers and a strong collaboration between the involved clinicians and biologists to reconcile currently controversial conclusions from different studies (Plotton et al, 2015;Rohayem et al, 2015).…”
Section: Fertilitymentioning
confidence: 99%
“…Previous studies showed that sperms are more likely to be retrieved in younger men with Klinefelter syndrome. 26,27 In our study, the man with nonmosaic Klinefelter syndrome was 42 years old and might have passed the window of opportunity for successful sperm retrieval. The two patients with mosaic Klinefelter syndrome were 34 and 47 years old, respectively.…”
Section: Discussionmentioning
confidence: 75%
“…Based on current literature, the recommended age range to consider sperm retrieval among individuals with KS is 15-30 years (3,9,10). Medical professionals who care for individuals with KS have a responsibility to become educated on this topic and offer referrals to fertility specialists to (I) provide comprehensive counseling about the current options along with acknowledging their experimental nature; and (II) consider potential ethical implications in each individual case (6,11).…”
mentioning
confidence: 99%